Sound categorization by crocodilians - Julie Thévenet; Mounia Kehy; Nicolas Boyer; Aurélie Pradeau; Léo Papet; Etienne Gaudrain; Nicolas Grimault; Nicolas Mathevon (iScience, 2023)
Summary: Rapidly sorting the information contained in a stream of stimuli is a major challenge for animals. One cognitive mechanism for achieving this goal is categorization, where the receiving individual considers a continuous variation of a stimulus as belonging to discrete categories. Using playback experiments in a naturalistic setup, here we show that crocodiles confronted with an acoustic continuum ranging from a frog call to a crocodile call classify each acoustic variant into one of these two categories, establishing a meaningful boundary where no acoustic boundary exists. With GO/NO-GO experiments, we then observe that this boundary is defined along the continuum following learning. We further demonstrate that crocodilians rely on the spectral envelope of sounds to categorize stimuli. This study suggests that sound categorization in crocodilians is a pre-wired faculty allowing rapid decision-making and highlights the learning-dependent plasticity involved in defining the boundary between sound categories.